The Role of the Women’s Organization ‘WIsSNU’ in the Internalization of Character Values in Pesantren - Mustikamah, Mustikamah; Na’imah, Farida Ulvi; Qutsiyah, Dewi Afiatul (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2025)
This study examines the internalization of character values in the activities of the Women’s Organization “WIsSNU” at the International Standard Madrasah (MBI) Amanatul Ummah. The research focuses on: (1) identifying the programs and events organized by WIsSNU, and (2) analyzing how character values are internalized through these activities. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The findings show that WIsSNU implements two categories of organizational programs: major events and minor events. Major events include PAKARSAMBI, Ponpesnu, and the MBF (MBI Big Fair). Minor events consist of Islamic Holiday Celebrations (HBI), such as the Prophet’s Birthday, Isra’ Mi’raj, and Nuzulul Qur’an (Ramadhan), as well as National Commemoration Days (HKN), such as the National Awakening Day. These activities serve not only as organizational traditions but also as media for character education. Character values identified by the Ministry of National Education are mostly reflected in these programs. Out of 18 values, 16 were found to be well-internalized, including religiosity, honesty, tolerance, discipline, hard work, creativity, democracy, curiosity, national spirit, love of the motherland, appreciation of achievement, communication skills, peace, social care, responsibility, and environmental awareness. Two values—independence and interest in reading—were not yet fully integrated. In conclusion, WIsSNU organizational programs significantly contribute to character education by embedding most of the core values through both major and minor events.